Kebijakan Pertahanan Indonesia 1998-2010 dalam Merespon Dinamika Lingkungan Strategis di Asia Tenggara - Iwan Sulistyo (Andalas Journal of International Studies (AJIS))
This article aims to analyze the response of Indonesia in an effort to counterbalance the development of military power in Southeast Asia during the 1998-2010 periods. This response is placed on the dimensions of the development policy of Indonesia's defense posture. The author uses a case study design. Through analysis of various documents, books, journals, and other sources as well as interviews with several experts in the field of defense and military, the author argues that Indonesia's defense posture development policy (land, sea, and air) in response to the military development in the countries of the Southeast Asia region during 1998-2010 period was intended to achieve more deterrent power than building an offensive force. The policy was made in light of the perception that the countries in Southeast Asia had the potential to threaten the security and sovereignty of Indonesia. Meanwhile, Indonesia's ability to build up military strength in the upper levels was very limited deterrent. Limited sources of funding and political support as well as weaknesses in analyzing the strategic environment of the region led to the development of the policy could not achieve the level of deterrent and also have not gotten to the point'strategic stability'. Indonesia was plagued by the problems of arms embargo by foreign countries and still has problems in the institutionalization of research and development.